SOCIOLOGICAL AND JURIDICAL ANALYSIS OF THE ESTABLISHMENT OF THE OMNIBUS LAW IN CREATION WORK FIELD CLUSTER (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Abstrak Proses pembentukan Undang-undang terutama Omnibus law Undang-undang Cipta Kerja adalah hal yang sangat baru. Masyarakat perlu waktu untuk memahami Teknis perundang-undangan tersebut. Namun juga dalam Pasal UU Cipta Kerja ini terdapat kejanggalan-kejanggalan yang mengakibatkan terjadinya demo di berbagai Kota di Indonesia. Dilihat dari aspek Sosiologis dan yuridis pembentukan Undang-undang ini perlu dianalisis lebih lanjut. Mengingat faktor pendorong terbesar Pemerintah mempentuk Undang-undang ini adalah untuk mempermudah pengusaha berinvestasi di Indonesia yang akan membutuhkan banyak tenaga kerja, sehingga penggangguran dapat teratasi. Kata Kunci : Omnibus law UU Cipta Kerja, Sosiologis, dan Yuridis.   Abstrak The process of forming laws, especially the Omnibus law, is a very new thing. People need time to understand the technicalities of these laws. However, this Article of the Job Creation Law also contains anomalies which have resulted in demonstrations in various cities in Indonesia. Viewed from the sociological and juridical aspects, the formation of this Law needs to be further analyzed. Considering that the biggest driving factor for the Government to form this Law is to make it easier for entrepreneurs to invest in Indonesia which will require a lot of labor, so that unemployment can be overcome. Keywords: Omnibus law UU Cipta Kerja, Sociological, and Juridical.